Wahana Edukasi Kreatif Sebagai Sarana Peningkatan Life Skill Siswa SD Bernuansa Alam Desa Darsono - Cahyaningtyas, Cindy Dwi; Widayanti, Ayu; Zahra, Mutiara Shofia; Widayanti, Anis; Miranda, Yussy; Rusdianto, Rusdianto (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
Darsono Village is a village located in Arjasa District, Jember Regency, East Java. The economic condition in Darsono Village is relatively low and exacerbated by low literacy skills. Darsono Village has several potentials, such as empty land, beautiful village atmosphere and various facilities in the village. Therefore, we carry out a service program that focuses on improving the quality of formal education through the program "Edu Nature Park: Creative Education Vehicle as a Means of Improving the Life Skills of Elementary School Students with Natural Nuances in Darsono Village, Jember Regency". Edu Nature Park is a fun educational program that refers to nature in Darsono Village. The problem in Darsono Village is that there are still cases of school dropouts due to economic factors and underage marriages to the low interest in reading by the community. The majority of children in Darsono Village often use their time by playing. The method of empowering rural communities is carried out in full in the field (offline) using the PRA (Participatory Rural Appraisal) method.